Guidelines for the Pastoral Care of the Divorced and Remarried in Czechia after Amoris laetitia - Monika Menke (Kościół i Prawo)
The article summarizes the Czech way of searching and creating possible guidelines of the Bishops' Conference or directives of individual bishops after the Post-synodal Apostolic Exhortation Amoris laetitia of Pope Francis. It discusses the establishments of a commission of experts, refers to foreign opinions that inspired the commission in its work, and outlines the lack of consensus among the bishops. Thus, the Bishops’ Conference failed to draw up uniformed guidelines on the subject. One of the bishops (the Diocese of Plzeň), after some time of searching for a solution, finally issued his own diocesan directive in the spring of 2023, the content of which is also presented in the text of the article.